2001
DOI: 10.1111/j.1572-0241.2001.03694.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transjugular Intrahepatic Portosystemic Shunt Formation on Portal Hypertensive Gastropathy and Gastric Circulation

Abstract: It is considered that TIPS may have a beneficial effect on PHG at least for a short time. The mechanism by which PHG improves may be closely related to the improvement of the injured gastric perfusion in cirrhotic patients with PHG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…As discussed below, other data supporting an association between PHG and portal hypertension include resolution of PHG after intervention to decrease portal hypertension, including pharmacotherapy [74][75][76][77][78] , transjugular intrahepatic portosystemic shunt (TIPS), or liver transplantation [74] . Contrariwise, a decided minority of studies showed no significant association between severity of portal hypertension and rate of PHG [8,9,16,26,28,30,31,47,54,67] .…”
Section: (50%) Not Reported Not Reportedmentioning
confidence: 99%
See 3 more Smart Citations
“…As discussed below, other data supporting an association between PHG and portal hypertension include resolution of PHG after intervention to decrease portal hypertension, including pharmacotherapy [74][75][76][77][78] , transjugular intrahepatic portosystemic shunt (TIPS), or liver transplantation [74] . Contrariwise, a decided minority of studies showed no significant association between severity of portal hypertension and rate of PHG [8,9,16,26,28,30,31,47,54,67] .…”
Section: (50%) Not Reported Not Reportedmentioning
confidence: 99%
“…Makhija et al [118] described in PHG a decrease in gastric mucosal blood flow, an increase in the submucosal and muscular layer blood flow, and a net increase in total gastric blood flow. Mezawa et al [76] using a laser Doppler flowmeter to measure gastric mucosal blood flow and near-infrared endoscopy to measure total gastric blood flow, reported decreased mucosal blood flow and increased total blood flow in patients with PHG. These results reversed after undergoing TIPS, with an increase in mucosal blood flow and a decrease in total blood flow.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…PHG is mainly detected in patients with more advanced liver disease and in those previously receiving endoscopic haemostatic treatment for EV and GV (prevalence 11-80%) [129,130]. Incidence of acute bleeding and related mortality are quite low (3% and 12.5% at three years, respectively) [131][132][133].…”
Section: Tips Is Not Indicated For the Prophylaxis Of First Variceal mentioning
confidence: 99%